LANSKAP KOLONIAL KOTA BAUBAU SEBUAH PUSAKA PENINGGALAN MASA KOLONIAL DI SULAWESI TENGGARA - Ray March Syahadat; Nurhayati H.S. Arifin; Hadi Susilo Arifin (Paramita: Historical Studies Journal)
Baubau is appointed as one of heritage cities in Indonesia because it has many historical inheritances. Although Baubau becomes an autonomous region in 2001, some historical records show that the city has been existed long time ago and passed some phases. One of those phases is the development era by the Dutch Indies Government. There are many inheritances from colonial period in the city even it is called as the largest in the Province of Southeast Sulawesi. Unfortunately, there are not many research and inventory by related stakeholders toward the colonial heritages in the city. This research aims to record or to list of current assets and to analyze the landscape characteristics of colonial heritages located in Baubau. The result shows that there are four historical landscapes which save the colonial heritage objects namely the colonial ladscape and early independence day (51 objects), Palabusa (4 objects), Wakonti (1 object), and Chinatown (5 objects). The character which constructs of the three landscapes generally consist of buildings, structures, and monuments with art deco style.